Review of Dissomphalus Ashmead (Hymenoptera, Bethylidae) from Panama, with key to the Central American species - Brito, Chirlei D.; Azevedo, Celso O. (Zootaxa, 2017)
Sixty-four species of Dissomphalus from Panama are recognized, 31 are described and illustrated as new to science: D. abarus sp. nov., D. afestus sp. nov., D. arbeius sp. nov., D. ardonius sp. nov., D. areius sp. nov., D. aretisus sp. nov., D. arteobius sp. nov., D. arteus sp. nov., D. asfartus sp. nov., D. asitius sp. nov., D. azagus sp. nov., D. borus sp. nov., D. citus sp. nov., D. ettus sp. nov., D. geortus sp. nov., D. ibocius sp. nov., D. ibrastus sp. nov., D. ilarius sp. nov., D. iozus sp. nov., D. isortus sp. nov., D. isteus sp. nov., D. racarus sp. nov., D. raziogus sp. nov., D. sartus sp. nov., D. teobus sp. nov., D. teraus sp. nov., D. terbius sp. nov., D. tisinus sp. nov., D. trisus sp. nov., D. urazius sp. nov. and D. ubracus sp. nov.. Eight species are registered for the first time from Panama: D. angulatus Azevedo, D. galeatus Alencar & Azevedo, D. infissus Evans, D. persontaus Redighieri & Azevedo, D. pilus Alencar & Azevedo, D. politus Ashmead, D. pronus Alencar & Azevedo and D. vallensis Evans. Eighteen species had their known distribution broadened in the country: D. bilobatus Azevedo, D. brasiliensis Kieffer, D. cervoides Azevedo, D. coronatus Alencar & Azevedo, D. culteratus Alencar & Azevedo, D. curvifoveatus Azevedo, D. dilatatus Azevedo, D. geniculatus Azevedo, D. gilvipes Evans, D. guttus Azevedo, D. intradentatus Azevedo, D. piscicercus Azevedo, D. plaumanni Evans, D. punctatus (Kieffer), D. rettenmeyeri Evans, D. rufipalpis Kieffer, D. strepsus Azevedo and D. unitus Azevedo. Seven species previously recorded from Panama were not found in the studied material: D. altivolans Evans, D. apertus Kieffer, Alencar & Azevedo, D. declinatus Alencar & Azevedo, D. latus Azevedo, D. ramosus Alencar & Azevedo, D. strabus Azevedo and D. subdeformis Azevedo. A key to species of Dissomphalus from Central America is provided.